Improving Relationship-Based Feeding of Infants and Young Children with Disabilities: Developing a Guideline for Practice. - Henton, Patricia; Howe, Tsu-Hsin (Open Journal of Occupational Therapy (OJOT))
Feeding is a significant co-occupation of young children and their caregivers, unfolding in a social context. While addressing feeding challenges comprehensively because multiple contributing factors, the social-emotional dimension is often overlooked. This paper proposes a relationship-based feeding guideline to help occupational therapists incorporate this critical component. Centered on the childcaregiver dyad, the guideline prioritizes supporting the developmental, social-emotional, and environmental needs of the child. The guideline employs a biopsycho-ecological framework and familycentered approach, emphasizing caregiver training for promoting positive interaction. Actively involving caregivers and employing caregiver-child coaching facilitates the learning of developmentally appropriate feeding strategies that are then applied at home. This guideline outlines the evaluation and intervention needed for improving feeding and mealtime participation, while concurrently strengthening the caregiverchild relationship and bonding. This paper articulates assessments and indicators specific to relationship-based feeding. General and specific intervention principles focus on providing support and guidance to caregivers, addressing the child's developmental and social-emotional needs during feeding. Practical applications for occupational therapists delineate caregiver guidance and caregiver-child coaching components of the guideline, supplemented by a case example illustrating a relationship-based feeding intervention.